Pendidikan Lingkungan Berkelanjutan di Sekolah Sungai Karang Mumus sebagai Referensi Bagi Katekese Lingkungan - Oktavia Kaha; Komela Avan; Gregorius Verensius Era (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2020)
The purposes of this research are to find whether the environmental educations in River School of Sungai Karang Mumus, named SeSuKaMu, meets the standard of sustainable environmental education, and it could be the reference for environmental catechesis. The result shows that SeSuKaMu has grew in sustainable environmental education standard, although they still have to raising more in implementation. Environmental education for sustainability elements consist of more future–oriented, critical of the pre-dominant market and consumption driven society, sensitive to context, more systematic in dealing with complexity, more community and solidarity-oriented, less concerned with product, more concerned with process (creating the right conditions for social learning), more open to new ways of thinking and doing, and preoccupied with linking social, economic and environmental equity at the local, regional and global levels. The elements could be find in SeSuKaMu, although they are still in small-growing level. As the conclusion, the sustainability orientation of SeSuKaMu could give the inspiration and be the reference for catechetical program based on Catholic theology.